2021
DOI: 10.1038/s41598-021-96385-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lipid emulsions on the formation of Escherichia coli–Candida albicans mixed-species biofilms on PVC

Abstract: Patients receiving lipid emulsions are at increased risk of contracting catheter-related bloodstream infections (CRBSIs) in the clinic. More than 15% of CRBSIs are polymicrobial. The objective of this study was to explore the effects of lipid emulsions on the formation of Escherichia coli (E. coli)–Candida albicans (C. albicans) mixed-species biofilms (BFs) on polyvinyl chloride (PVC) surfaces and the underlying mechanism. Mixed-species BFs were produced by coculturing E. coli and C. albicans with PVC in vario… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…For the most studied C. albicans , it is known that biofilm formation is linked to the transition from yeast to hyphal mode [ 33 ]. In dual biofilms of C. albicans and bacteria, different distributions have been described, such as preferential adherence to hyphae for streptococci [ 34 , 35 ] and S. aureus [ 36 ], adherence to both hyphae and yeast forms for E. coli [ 5 , 37 ], Clostridium perfringens , Bacteroides fragilis , Enterococcus faecalis or K. pneumoniae [ 37 ]. Here, for dual biofilms of C. parapsilosis , generating only pseudohyphae, and E. cloacae complex ( E. bugandensis ), we observed that the bacterium adheres to yeasts, but a more detailed observation of biofilms suggested that the bacterium predominates on the bottom layer of the biofilms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the most studied C. albicans , it is known that biofilm formation is linked to the transition from yeast to hyphal mode [ 33 ]. In dual biofilms of C. albicans and bacteria, different distributions have been described, such as preferential adherence to hyphae for streptococci [ 34 , 35 ] and S. aureus [ 36 ], adherence to both hyphae and yeast forms for E. coli [ 5 , 37 ], Clostridium perfringens , Bacteroides fragilis , Enterococcus faecalis or K. pneumoniae [ 37 ]. Here, for dual biofilms of C. parapsilosis , generating only pseudohyphae, and E. cloacae complex ( E. bugandensis ), we observed that the bacterium adheres to yeasts, but a more detailed observation of biofilms suggested that the bacterium predominates on the bottom layer of the biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…[ 1 ]. Several studies reported the occurrence of polymicrobial CRBSI, as well as the increase in their incidence [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…E. coli is a frequently isolated Gramnegative bacterium in bloodstream infections 51,52) . The interactions between E. coli and C. albicans in cross-kingdom dual-species biofilms have been studied in vitro [53][54][55][56] . An in vivo experimental system using silkworms for the cross-kingdom dual-species biofilm by E.coli and C. albicans was established using the clinical E. coli isolate RB-3, known for its high biofilm-forming capacity in vitro 50) .…”
Section: Silkworm Infection Model For Evaluating Crosskingdom Dual-sp...mentioning
confidence: 99%